Backscattered electron imaging of resin-embedded sections. (15th June 2018) - Koga, Daisuke; Kusumi, Satoshi; Watanabe, Tsuyoshi
Abstract : This review gives an overview of recent developments in scanning electron microscopy (SEM) methods with specific focus on the section-face imaging and serial section SEM methods that we recently established. Abstract: Scanning electron microscopes have longer focal depths than transmission electron microscopes and enable visualization of the three-dimensional (3D) surface structures of specimens. While scanning electron microscopy (SEM) in biological research was generally used for the analysis of bulk specimens until around the year 2000, more recent instrumental advances have broadened the application of SEM; for example, backscattered electron (BSE) signals under low accelerating voltages allow block-face and section-face images of tissues embedded in resin to be acquired. This technical breakthrough has led to the development of novel 3D imaging techniques including focused ion beam SEM, serial-block face SEM and serial section SEM. Using these new techniques, the 3D shapes of cells and cell organelles have been revealed clearly through reconstruction of serial tomographic images. In this review, we address two modern SEM techniques: section-face imaging of resin-embedded tissue samples based on BSE observations, and serial section SEM for reconstruction of the 3D structures of cells and organelles from BSE-mode SEM images of consecutive ultrathin sections on solid substrates.